Effect of cell size on the compressive properties of interlocking flax composite structures - Mohamed Yusoff, Mohd Zuhri; Nasrudin, Muhammad Asyraf; Salit, Mohd Sapuan; Hassan, Mohamad Zaki (Centre for Advanced Research on Energy, Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka, 2018)
This paper investigates the cell size effect on the compression properties of square interlocking structures made of flax/polylactide (flax/PLA) composite. Three cell sizes have been investigated, these being 10 mm, 20 mm and 40 mm. The core and skins of the structure are made of three layers of flax/PLA composite and manufactured using hot press machine. The results indicated that the compression strength increases as the relative density of the structure increased. It is also observed that the larger cell size offered a higher energy-absorbing value than the smaller cell size with a similar thickness.